2020
DOI: 10.5430/ijhe.v9n6p286
|View full text |Cite
|
Sign up to set email alerts
|

Management of Student Entrepreneurship Development at the West Java-Indonesia Private Islamic College

Abstract: This study aims to explore the relations between the factors of the start-up environment and entrepreneurial intentions of students in universities in Vietnam and the Philippines by com­bining key elements of theory of reasoned action, theory of planned behaviour, theory of en­trepreneurial events and model of entrepreneurial potential. Research findings were expected to test the appropriateness of this proposed model in the context of Vietnam and the Philippines. A bilateral survey was carried out among 819 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…According to the theory Rusdiana (2015), which is in line with this research, schools must also pay attention to several factors that contribute to the success of SBM, including the first factor is the principal, all school personnel, and good school management; second, there is participation; third, there is government support; and fourth, there is professionalism from all parties. This is in line with earlier research by Susetyo (2013), who concluded that school principals' managerial skills had a beneficial impact on the adoption of school-based management and there are still challenges that must be overcome for it to be implemented.…”
Section: Supporting and Inhibiting Factors In Creating Excellent Scho...mentioning
confidence: 66%
“…According to the theory Rusdiana (2015), which is in line with this research, schools must also pay attention to several factors that contribute to the success of SBM, including the first factor is the principal, all school personnel, and good school management; second, there is participation; third, there is government support; and fourth, there is professionalism from all parties. This is in line with earlier research by Susetyo (2013), who concluded that school principals' managerial skills had a beneficial impact on the adoption of school-based management and there are still challenges that must be overcome for it to be implemented.…”
Section: Supporting and Inhibiting Factors In Creating Excellent Scho...mentioning
confidence: 66%
“…This might be an opportunity for social entrepreneurs to make social entrepreneurship "the future of business". The word sociopreneurship comes from social and entrepreneurship, which means a person or organization who understands social problems and uses entrepreneurial abilities to make social change (Rusdiana et al, 2020). Bornstein & Davis (2010) added that the practice of social entrepreneurship plays an important role through new approaches, ideas, or new models in the form of poverty alleviation, welfare improvement, wealth creation, environmental preservation, and legal aid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entrepreneurship, from a global perspective, has become a global proposition and is increasingly favored and recognized by countries around the world [1]. Because under the background of today's increasing development of information technology, entrepreneurial activities can not only promote technological innovation, accelerate the upgrading of industrial structure, and improve labor productivity, but also do it, promote labor employment, and stimulate the creative potential of social members [2].…”
Section: Introductionmentioning
confidence: 99%